2022
DOI: 10.1007/s10695-022-01052-w
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant responses of gills, intestines and livers and blood immunity of common carp (Cyprinus carpio) exposed to salinity and temperature stressors

Abstract: Aquaculture activity is affected by various environmental factors, including water salinity and high temperatures. The present study investigated the impact of using varying water salinity (0, 5, 10, 15 and 20 ppt) on the growth behavior, immune responses and antioxidative responses of common carp. Fish were raised under optimal conditions except for water salinity for 8 weeks; fish were then subjected to high-temperature stress (32 °C) for 48 h. The results indicated a reduced final weight (FBW), weight gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…In aquaculture, alterations in the spectrum can trigger oxidativereductive reactions in crustaceans, leading to fluctuations in the activity of antioxidant enzymes and the levels of oxidative products [12,19]. Among these, SOD and MDA serve as vital markers for the antioxidant capacity of aquatic organisms [30,31]. The findings from our experiment reveal that the SOD activity of juvenile redclaw crayfish under green, blue, and white light spectra is markedly lower compared to that under the red light spectrum.…”
Section: Discussionmentioning
confidence: 66%
“…In aquaculture, alterations in the spectrum can trigger oxidativereductive reactions in crustaceans, leading to fluctuations in the activity of antioxidant enzymes and the levels of oxidative products [12,19]. Among these, SOD and MDA serve as vital markers for the antioxidant capacity of aquatic organisms [30,31]. The findings from our experiment reveal that the SOD activity of juvenile redclaw crayfish under green, blue, and white light spectra is markedly lower compared to that under the red light spectrum.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, we are aware of only one study investigating the combination of salinity and temperature. In this study, Dawood and colleagues [ 122 ] demonstrate that hypersalinity in common carp ( Cyprinus carpio ), a freshwater fish, reduced antioxidative indices (SOD, CAT, GPx), lysozyme and respiratory burst activity. Additional acute heat stress further exaggerated this immunosuppression, indicating a synergistic effect of these two stressors.…”
Section: Interactive Effects Of Multiple Climate Change-related Stres...mentioning
confidence: 66%
“…In freshwater fish, salinity levels beyond their physiological limits naturally lead to an impairment of the immune response, and to lowered survival in response to infection [ 121 , 122 ]. Moderate (up to 10 ppt, control 0.4 ppt, physiological maximum 15 ppt [ 123 ]) chronic (20 days) hypersalinity increased lysozyme and alternative complement pathway activity in striped catfish ( Pangasianodon hypophthalmus ) [ 121 ] (see electronic supplementary material, table S1).…”
Section: Environmental Stressorsmentioning
confidence: 99%
“…The blood total protein, albumin, and globulin levels were markedly reduced in fish exposed to ammonia, high salinity (15 ppt), and both of them. Under high salinity conditions, common carp (Dawood et al 2022a ) showed reduced blood proteins. The oxidative stress induced by ammonia and high salinity results in loss of appetite malnutrition, thereby reducing protein metabolism in the fish’s entire body (Zarantoniello et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%